Место трaдиционной культуры в процессе модернизaции Китaя (ҚазҰУ хабаршысы. Шығыстану сериясы, 2018)
In article authors consider the attitude of governors of China towards traditional culture during moderntimes, are also analyzed assessment various political a current for a role of traditional culture in thecourse of modernization of China. Authors note that if earlier communistic leaders criticized traditionalvalues, then now they are actively used for ensuring support by the population of policy of KKP.